2019
DOI: 10.5507/bp.2019.047
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic CT features of pheochromocytomas - probability model calculation tool based on a multicentric study

Abstract: Objectives. The aim of the study was to evaluate the CT features of adrenal tumors in an effort to identify features specific to pheochromocytomas and second, to define a feasible probability calculation model. Methods. This multicentric retrospective study included patients from the period 2003 to 2017 with an appropriate CT examination and a histological diagnosis of an adrenal adenoma, pheochromocytoma, adrenocortical carcinoma, or metastasis. In total, 346 patients were suitable for the CT image analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…All patients with adrenal incidentaloma with tumour density more than 10 HU should be screened for PPGL even in the absence of hypertension [18,[32][33][34][35]. This is also justified by the finding that hypertension among patients with adrenal incidentalomas is not more frequent in patients with PPGL than in those without PPGL [17].…”
Section: Adrenal Incidentalomamentioning
confidence: 99%
“…All patients with adrenal incidentaloma with tumour density more than 10 HU should be screened for PPGL even in the absence of hypertension [18,[32][33][34][35]. This is also justified by the finding that hypertension among patients with adrenal incidentalomas is not more frequent in patients with PPGL than in those without PPGL [17].…”
Section: Adrenal Incidentalomamentioning
confidence: 99%
“…The myocardial tissue of the left atrium extends into the outer layer of the pulmonary vein wall, which, in turn, forms a myocardial sleeve. This extended myocardial sleeve is the release point for the abnormal potential activity, and it has been demonstrated that approximately 94% of the abnormal potential triggers are from the pulmonary veins [ 18 ]. Supraventricular arrhythmias, such as atrial fibrillation, generally have a long history, significant myocardial fibrosis, more complications, high risk of stroke with drug therapy, poor efficacy, and arrhythmogenic effects with the long-term application of antiarrhythmic drugs in such patients.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, endocrinological data are not usually available in the other previous articles mentioned in this discussion. However, our own data regarding adrenal mass diameter have been published in another article, in which the study group partially overlaps with the study group in this manuscript [21].…”
Section: Discussionmentioning
confidence: 78%